Comprehensive analysis of repetitive extragenic palindrome sequences identified in bacteria and archaea using a new web-based tool, RepRanger - Oleg N. Murashko; Connor Morgan-Lang; Chen-Hsin Albert Yu; Hsin-Nan Lin; Anna Chao Kaberdina; Shin-Yu Kung; Vladimir R. Kaberdin; Sue Lin-Chao (mSphere)
ABSTRACT Repetitive extragenic palindromic (REP) sequences were first discovered in the intergenic regions of Escherichia coli and later found in phylogenetically distinct bacterial species. However, their biological roles and sequence conservation remain unclear. Considering the growing number of microbial genome sequencing and annotation projects, along with the lack of online tools for REP identification, we developed a new web-based platform, RepRanger, to rapidly identify and annotate putative palindromic elements, including REPs. Using RepRanger, we identified >4,000 REPs in the E. coli MG1655 genome. Moreover, 81 (~52%) of its 157 small noncoding RNAs (sRNAs; known to regulate gene expression) contain REPs. Further analysis using RepRanger, alongside other bioinformatics tools, yielded 10 REP consensus motifs. Notably, REPs potentially involved in translational control (i.e., located within 15 nucleotides downstream of an open reading frame) primarily host motif 4, whereas REPs present in sRNAs predominantly encoded motif 9. Putative targets of REP-containing sRNAs include genes that rewire metabolic pathways in response to environmental changes, indicating that REPs likely contribute to bacterial adaptation. We also reveal that REP consensus motifs are similar across pathogenic and environmental E. coli strains but not commensal and laboratory ones. We employed RepRanger to search for REPs and confirm that they are present across bacteria and archaea. Furthermore, we uncovered similarities in REP sequences between bacterial and archaeal genomes. Thus, we demonstrate that RepRanger represents a versatile tool for discovering REPs in bacteria and archaea, providing new insights into their functions and sequence diversity.IMPORTANCERepetitive extragenic palindromic (REP) sequences were first discovered in Escherichia coli, but their biological roles, diversity, and sequence conservation remain unclear. We have developed a web-based tool, RepRanger, to identify and annotate putative palindromic elements, including REPs. Using RepRanger, we identified approximately 4,000 REPs in the E. coli MG1655 genome. We show that >50% of small noncoding RNAs (sRNAs) contain REPs. The predicted functions of REP-containing sRNAs indicate that REPs likely contribute to bacterial environmental adaptability. In addition, we have discovered REPs in pathogenic, environmental, and commensal E. coli, allowing us to assess their sequence similarity. We show that REPs are widely present in bacterial and archaeal genomes and share some sequence similarities. Our comparison of REPs in annotated genomes broadens the current understanding of REP sequence diversity, conservation, and function.